Perfil fenotípico e genotípico de uma cepa de Escherichia coli multirresistente a antibióticos, isolada do lago Água Preta, Belém, Pará. - LIMA, Alyne Cristina Sodré (Instituto Federal do Amapá, 2021)
The present work aimed to describe the phenotypic and genotypic profile of a bacterium strain resistant to last resort antibiotic, isolated from the Água Preta lake, water supply source in Belém, Pará. The phenotypic characterization methods were Gram staining, direct microscopy and in vitro sensitivity test. For genotypic characterization purposes, genomic DNA extraction, species differentiation through Quadruplex PCR and PCR for identification of resistance genes were performed. The C40A strain was identified as an Escherichia coli belonging to filogroup D. The bacterium was resistant to 87.5% of the clinically available antibiotics for the treatment of bacterial infections and susceptible to only 12.5% (Imipenem and Kanamycin). The presence of the blaCTX gene and the mobile elements Intl1 and Intl2 were identified. These genetic components were markedly associated with the expression of antibiotic resistance profiles.